Statistics on Ethnic Diversity in the Land of Papua, Indonesia. Issue 3 (27th June 2016) - Ananta, Aris; Utami, Dwi Retno Wilujeng Wahyu; Handayani, Nur Budi
Abstract: This paper aims to quantitatively uncover ethnic diversity in multi‐ethnic Land of Papua, an Indonesian region with a large inflow of migration and rising ethno‐based movement, consisting of the Provinces of Papua and West Papua. It produces statistics on ethnic diversity in the Land of Papua, utilizing the tabulation provided by Statistics‐Indonesia based on the raw, 100 per cent, data set of the 2010 population census. It uses three measurements of ethnic diversity. First is ethnic fractionalization index, showing the degree of ethnic heterogeneity. Second is ethnic polarization index, examining the existence of few relatively large ethnic groups of almost the same sizes. Third is a comparison of percentages between migrant and Papuan groups. It finds that the Land of Papua is ethnically very heterogeneous, but not polarized. West Papua is more heterogeneous, but Papua is more polarized. However, seen from a dichotomy between migrants and Papuans, West Papua is very polarized. In‐migration may have increased the probability of having ethnic conflicts in the region but does not change the probability of the intensity of the conflicts. Therefore, ethnic conflicts should be anticipated whenever making programmes that involve in‐migrants or entice people to migrate into the Land of Papua.